Crystalline structure of pulverized dental calculus induces cell death in oral epithelial cells. (20th November 2017) - Ziauddin, S. M.; Yoshimura, A.; Montenegro Raudales, J. L.; Ozaki, Y.; Higuchi, K.; Ukai, T.; Kaneko, T.; Miyazaki, T.; Latz, E.; Hara, Y.
Abstract : Background and Objective: Dental calculus is a mineralized deposit attached to the tooth surface. We have shown that cellular uptake of dental calculus triggers nucleotide‐binding oligomerization domain‐like receptor family pyrin domain‐containing 3 (NLRP3) inflammasome activation, leading to the processing of the interleukin‐1β precursor into its mature form in mouse and human phagocytes. The activation of the NLRP3 inflammasome also induced a lytic form of programmed cell death, pyroptosis, in these cells. However, the effects of dental calculus on other cell types in periodontal tissue have not been investigated. The aim of this study was to determine whether dental calculus can induce cell death in oral epithelial cells. Material and Methods: HSC‐2 human oral squamous carcinoma cells, HOMK107 human primary oral epithelial cells and immortalized mouse macrophages were exposed to dental calculus or 1 of its components, hydroxyapatite crystals. For inhibition assays, the cells were exposed to dental calculus in the presence or absence of cytochalasin D (endocytosis inhibitor), z‐YVAD‐fmk (caspase‐1 inhibitor) or glyburide (NLRP3 inflammasome inhibitor). Cytotoxicity was determined by measuring lactate dehydrogenase (LDH) release and staining with propidium iodide. Tumor necrosis factor‐α production was quantified by enzyme‐linked immunosorbent assay. Oral epithelial barrier function was examined by permeability assay. Results: Dental calculus induced cell death in HSC‐2 cells, as judged by LDH release and propidium iodide staining. Dental calculus also induced LDH release from HOMK107 cells. Following heat treatment, dental calculus lost its capacity to induce tumor necrosis factor‐α in mouse macrophages, but could induce LDH release in HSC‐2 cells, indicating a major role of inorganic components in cell death. Hydroxyapatite crystals also induced cell death in both HSC‐2 and HOMK107 cells, as judged by LDH release, indicating the capacity of crystal particles to induce cell death. Cell death induced by dental calculus was significantly inhibited by cytochalasin D, z‐YVAD‐fmk and glyburide, indicating NLRP3 inflammasome involvement. In permeability assays, dental calculus attenuated the barrier function of HSC‐2 cell monolayers. Conclusion: Dental calculus induces pyroptotic cell death in human oral epithelial cells and the crystalline structure plays a major role in this process. Oral epithelial cell death induced by dental calculus might be important for the etiology of periodontitis.